Legalizing gender inequality : courts, markets, and unequal pay for women in America - Nelson, Robert L., 1952-; Bridges, William P. (Structural analysis in the social sciences, 1999)
"Equal pay for men and women in the work force suffered a series of defeats in U.S. courts during the 1970s and 1980s and became the object of attack by a conservative administration and conventional economic wisdom. Yet the issue persists, unsolved, and continues to attract scholarly and popular attention. Building upon a new generation of research about institutions and the social construction of the market, the authors of Legalizing Gender Inequality challenge the existing theories of gender-based pay inequality and present a new, more realistic way to analyze the relationship between the market, pay differentials, and the law."--Jacket